Measurement of the relative branching fractions of B+ → h+ h'+ h'- decays - Aaij, Roel; Archilli, Flavio; Bachmann, Sebastian; Berninghoff, Daniel; Borsato, Martino; Dziewiecki, Michal; Frau, Giulia; Gerick, David; Grabowski, Jascha; Günther, Paul André; Han, Xiaoxue; Hansmann-Menzemer, Stephanie; et al. (Physical review, 2020)
The relative branching fractions of B+→h+h'+h'− decays, where h(') is a pion or kaon, are measured. The analysis is performed with a data sample, collected with the LHCb detector, corresponding to an integrated luminosity of 3.0 fb−1 of pp collisions. The results obtained improve significantly on previous measurements of these quantities, and are important for the interpretation of Dalitz plot analyses of three-body charmless hadronic decays of B+ mesons.
Im Titel ist sind die Pluszeichen und das Minuszeichen jeweils hochgestellt
Gesehen am 02.03.2021
The LHCb collaboration: R. Aaij, F. Archilli, S. Bachmann, D. Berninghoff, M. Borsato, M. Dziewiecki, G. Frau, D. Gerick, J. Grabowski, P.A. Günther, X. Han, S. Hansmann-Menzemer, J. Hu, M. Kecke, R. Kopecna, B. Leverington, P. Li, H. Malygina, J. Marks, S. Neubert, A. Piucci, and G. Zunica [und viele weitere]